Adaptasi Bahasa Asing Dalam Bahasa Bali - I Made Suweta (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
The use of Balinese language is currently not entirely pure, where its use is mixed with other languages or referred to as code switching or code mixing to facilitate understanding. Usually, speaking in local language (Balinese) is mixed with elements of foreign languages. The opposite can also occur in regional language (Balinese) mixed with foreign language elements. In educated people, it is often that the local language (Balinese) is mixed with elements of Indonesian and English and vice versa, all of these things will contribute to a mutually supporting vocabulary. Based on the background above, there are three problems, namely: (1) What is the process of foreign language adaptation in Balinese?, (2) What is the form of foreign language adaptation in Balinese, and (3) What is the impact of foreign language adaptation in Balinese language?In order to exist as a language of communication, Balinese language cannot only grow and rely on its vocabulary. Therefore, the Balinese language also adapts many foreign languages used in communication following the current developments in globalization. Adaptation of foreign languages in Balinese can be seen from the existence of several processes (Protesis, Epentesis, Paragogue, Afaraesis, Syncope, Apathope, Metathesis, Dissimilation, Assimilation, and Contractions), adaptations in the form of words and those used in sentences, and some impacts caused (positive and negative impacts). Indispensable awareness of the speakers to participate in the preservation of the Balinese language is highly required. Although the Balinese language requires adaptation of foreign languages to develop Balinese language in communicating in this global era, but the term of Balinese language that does exist, must be prioritized in the development of new terms.Keywords: Local languages, Foreign Languages, Foreign language adaptations in Balinese